An Overview of Microfinance Service Practices in Nepal - Sharma, Pushpa Raj (Journal of Nepalese Business Studies, 2012)
Microfinance is not simply banking for the poor; it is a development approach with a social mission and a private sector-based financial bottom line that uses tested and continually adjusted sets of principles, practices and technologies. The key to successful microfinance lies in the ability of the provider to cost-effectively reach a critical mass of clients with systems of delivery, market responsiveness, risk management and control that can generate a profit to the institution. Typically, this profit is ploughed back to ensure the long-term survival of the institution, i.e. the continuous provision of services demanded by its clients. The two long-term goals of microfinance are thus substantial outreach and sustainability. This article focus on microfinance services practices in Nepal on the basis of opinion survey. The Journal of Nepalese Business Studies Vol. Vii, No. 1, 2010-2011 Page : 1-16 Uploaded date: July 7, 2012